The bullet and the ballot box the story of Nepal's Maoist revolution - Adhikari Aditya (2014)
"In 1996, when Nepal's Maoists launched their armed rebellion, their ideology was widely considered obsolete and they had limited public support. By 2008 they had gained access to state power and their ambitious plan of social transformation dominated the national agenda. How did this become possible? The Bullet and the Ballot Box offers a rich and sweeping account of a decade of revolutionary upheaval. Adhikari draws on a broad range of sources, including novels, letters and diaries, to illuminate both the history and human drama of the Maoist rebellion. An indispensible guide to Nepal's recent history, the book also offers a fascinating case study of how communist ideology has been reinterpreted and translated into political action in the twenty-first century"--
Keywords: Communism -- Nepal -- History; Social change -- Nepal -- History; Elections -- Nepal -- History; Political participation -- Nepal -- History; HISTORY / Asia / India & South Asia; HISTORY / Revolutionary; POLITICAL SCIENCE / Political Ideologies / Communism & Socialism; Nepal -- History -- Civil War, 1996-2006.; Nepal -- Politics and government -- 1990-